A Proposed System for Securing Cryptocurrency Via the Integration of Internet of Things with Blockchain - Ghalwesh, Atef; Ouf, Shimaa; Sayed, Amr (International Journal of Economics and Financial Issues, 2020)
Nowadays the world discuss the problem of the cryptocurrency and shows several risks in dealing with this new investment or banning it by governments and the main issue of this paper is how can the third part ex: (exchange market for trading cryptocurrencies) avoid cybercriminal activities, In this paper, we will define only two of cybercriminals that related to the third part directly, First: Ransomware attacks and how the process of storing cryptocurrencies can be secured. Second: Black net in which many illegal trades could be done and how can the third part (governments) monitor the relationship between buyers and sellers to avoid this problem. In this paper, we propose a framework that proposed in anew exchange market by integrating blockchain technology and IOT (internet of things) to increase the security in the two processes that consider the main issues for the exchange market: first: storing the cryptocurrencies securely and avoid ransomware attacks, second: monitoring the transactions and avoid illegal business (black net) could happen through it. And we can implement this framework for special types of partially decentralized cryptocurrencies ex: NEO and Libra coin. Keywords: Cryptocurrency, Hyperledger, Ransomware, Black Net, Blockchain, Internet of Things JEL Classifications: E58, M15, K22 DOI: https://doi.org/10.32479/ijefi.9130